1992
DOI: 10.1159/000186826
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Pruritus and Skin Mast Cells

Abstract: The number of mast cells in the skin was evaluated in 25 patients with end-stage renal failure on different treatment modality (conservative, hemodialysis and peritoneal dialysis). According to the presence of pruritus, uremic patients were divided into two groups: group A, 13 patients with diffuse pruritus, and group B, 12 patients without pruritus. Controls were 6 age- and sex-matched healthy subjects. In comparison with patients without pruritus, patients with pruritus had mainly degranulated, diffusely spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 10 publications
1
40
1
2
Order By: Relevance
“…2,7,13 Sel mast tersebar secara difus di sepanjang kulit dan sebagian besar berdegranulasi. 9,16 Sel mast pada dermis terletak berdekatan ke saraf aferen C neuron terminal, dan interaksi antara struktur ini berperan penting dalam mediasi pruritus. 7 Sel mast akan melepaskan berbagai substansia seperti histamin, protease, interleukin-2, dan tumor necrosis factor.…”
Section: Patogenesisunclassified
See 1 more Smart Citation
“…2,7,13 Sel mast tersebar secara difus di sepanjang kulit dan sebagian besar berdegranulasi. 9,16 Sel mast pada dermis terletak berdekatan ke saraf aferen C neuron terminal, dan interaksi antara struktur ini berperan penting dalam mediasi pruritus. 7 Sel mast akan melepaskan berbagai substansia seperti histamin, protease, interleukin-2, dan tumor necrosis factor.…”
Section: Patogenesisunclassified
“…7 Sel mast akan melepaskan berbagai substansia seperti histamin, protease, interleukin-2, dan tumor necrosis factor. 7,16 Histamin telah dikenal luas sebagai pruritogenik yang secara langsung menstimulasi neuron terminal oleh reseptor H1.…”
Section: Patogenesisunclassified
“…The use of PMMA membranes has been shown to ameliorate the severity and frequency of pruritis [95] in HD patients due to adsorption of a 160,000 Dalton molecular weight molecule with stimulatory effect on mast cells [100]. PMMA membranes also efficiently adsorb β 2 -M (representative of middle molecules), where they have been shown to improve carpal tunnel syndrome or total joint pain score in HD patients [99].…”
Section: Adsorption Hemodialysismentioning
confidence: 99%
“…Plasma histamine levels were found to be increased in uremic patients, mainly in those with pruritus [5, 7, 8, 11, 15, 16], and some investigators have found a positive correlation between plasma histamine levels and pruritus [7, 8, 11, 15, 16], but this was not confirmed by others [5]. Serotonin has been reported to be a mediator of uremic pruritus – it causes itching when injected with prostaglandins –, and the results with the use of ketotifen, a stabilizer of mast cell membrane, in patients with uremic pruritus are encouraging [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin has been reported to be a mediator of uremic pruritus – it causes itching when injected with prostaglandins –, and the results with the use of ketotifen, a stabilizer of mast cell membrane, in patients with uremic pruritus are encouraging [15, 16]. Also ondansetron, a potent and selective inhibitor of 5-HT 3 receptors in the central and peripheral neural systems, has been used in some patients with severe pruritus due to cholestasis of various etiology, with satisfactory results [17, 18].…”
Section: Introductionmentioning
confidence: 99%